인성 교과교육 교육효과성 분석-성균관대학교 - 유홍준(Yoo, Hong Joon); 도승이(Doh, Seungyi); 고재석(Ko, Jaesuk) (교양교육연구, 2017)
본 연구는 성균관대학교에서 2013년부터 「논어」를 기반으로 시행하고 있는 인성 교과교육의 교육효과성을 파악하기 위해 평가 지표를 개발한 뒤 수강학생들을 대상으로 한 설문조사 자료를 분석하였다. 인성에 대한 개념 분석에 기반하여 인성지수 모형을 설정한 뒤 [성실], [배려], [정의], [책임]의 4가지 차원으로 이루어진 평가척도를 개발하였다. 2016년 2월에 사전조사(prestest)를 통해 측정도구의 타당성과 신뢰성을 살펴보았고, 이렇게 개발된 측정도구를 이용하여 성균인성 교과교육 이전과 이후(2016년 3월초와 6월중)에 각각 1차조사와 2차조사를 실시하여 그 차이점을 통한 효과성을 살펴보았다. 성균인성교육의 효과성 분석 결과, [성실]과 [책임] 차원에 대한 평균 점수가 높고 [배려]와 [정의] 차원에 대한 평균 점수는 상대적으로 낮은 것으로 나타났다. 인성교육이 통계적으로 유의미한 효과는 있지만 실질적 효과가 별로 크지 않게 나온 결과와 관련하여, 세 가지로 그 이유를 추론해 보았는데, 인성이 고착된 대학생들에 대한 인성교육의 실효성 미비, 연구 조사 척도 자체의 타당성 문제, 인성교육을 거치는 동안에 응답 학생들이 자성(自省)을 하게 되어서 자기 평가가 더 엄격해진 때문 등이다. This study analyze the survey data to evaluate the educational efficacy of humanity curriculum launched in SKKU since 2013 dependent on 「Analects of Confucius」. Based on the analysis of previous definitions of humanity, a model of humanity index with four dimensions(sincerity, solicitude, justice and responsibility) is developed. The reliability and validity of the measurement scale is checked through a pretest in February in 2016. By using this evaluation index, the first and the second survey were accomplished before and after the SKKU humanity classes in the spring semester of 2016(in early March and in the middle of June) for all of the students who took the course. The difference in these two test results is treated as an effect of the class. The analysis shows that SKKU students show a relatively higher level of score on sincerely and responsibility dimension while the average score on solicitude and justice dimension is relatively low. In regard to the result that the substantive effects of humanity education is not great regardless of its statistical significance, three aspects of plausible answer are considered. KCI Citation Count: 3